Anti-"negative-doping" testing: a new perspective in anti-doping research? - Lippi, G.; Sanchis-Gomar, F.; Banfi, G. (European Journal of Applied Physiology, 2012)
There is evidence that negative doping might not be limited to dog- or horseracing, so that a new perspective is challenging the already complicated setting of anti-doping testing, i.e., so-called anti-``negative-doping`` testing.